METHOD FOR DETECTING AND QUANTIFYING FUNGI AND BACTERIA USING FLOW CYTOMETRY - DUBERNET, Matthieu (2023)
The present invention relates to a method for simultaneously detecting and quantifying fungi and bacteria present in a divided solid containing organic-cellulosic materials. According to the invention, at least one first fluorochrome capable of binding with DNA and emitting, following excitation, at a wavelength equal to or higher than 599 nm and equal to or lower than 657 nm is added to the sample before said sample is introduced into the cytometer. La présente invention concerne une méthode de détection et quantification simultanée des fungi et des bactéries présentes dans un solide divisé contenant des matières organiques cellulosiques. Selon l ' invention, on ajoute dans ledit échantillon avant introduction dans ledit cytomètre, au moins un premier fluorochrome apte à se lier à l 'ADN et émettant, suite à une excitation, dans une longueur d'onde égale ou supérieure à 599 et égale ou inférieure à 657nm.